Psoriasis Eritroderma: Laporan Kasus - Riska Mordiana Putu; Nyoman Yudha Santosa (Cermin Dunia Kedokteran, 2025)
Introduction: Erythrodermic psoriasis (EP) is a rare type of psoriasis and can be life-threatening. EP requires intensive observation because the large area of the scaly skin increases the risk of secondary infection and sepsis, disrupts the regulation of body temperature, and causes loss of protein, electrolytes, and fuids. Case: Male, 37 years old, with reddish and scaly skin all over the body since 1 day, accompanied by pain and itch. The patient had a history of psoriasis with routine treatment. Discussion: Diagnosis is based on history and typical clinical fndings. The management is intravenous fuids, antibiotics, corticosteroids, antihistamines, and a combination of topical therapy. Conclusion: Erythrodermic psoriasis (EP) is a rare and potentially life-threatening type of psoriasis that requires close bservation, as it can lead to shock and organ failure.